2014
DOI: 10.4172/2167-0889.1000167
|View full text |Cite
|
Sign up to set email alerts
|

Levels and Values of Circulating Hematopoietic and Endothelial Progenitor Cells in Patients with Hepatocellular Carcinoma

Abstract: Objective: Development of HCC is associated with the process of angiogenesis and leads to the increment of the number of stem cells in the peripheral blood circulation. This study evaluated whether the level of hematopoietic stem cells and endothelial progenitor cells (HSCs & EPCs) could indicate the unfavorable tumour biology and the progress of disease in HCC. Methods: The study covered 146 HCC patients; 53 selected for liver resection, 49 for liver transplantation, 44 for palliation. Control consisted of 42… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 43 publications
3
6
0
Order By: Relevance
“…The mean percentages of circulating HSCs (%HSCs/ WBCs) were significantly reduced in the HCC patients, whereas the mean percentages of circulating EPCs within the HSCs subpopulation (% EPCs/HSCs) were significantly increased in the HCC patients compared to the controls. Our finding appears to be keeping with results published by Otto et al [32] who demonstrated that for a normal liver, high rate of HSCs together with low rate of EPCs is the standard. Yet, the occurrence of severe pathologic process within the liver, such as cirrhosis and particularly malignancy, inverses the relations between these cells leading to declining rates of hematopoietic cells and expanding rates of EPCs.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The mean percentages of circulating HSCs (%HSCs/ WBCs) were significantly reduced in the HCC patients, whereas the mean percentages of circulating EPCs within the HSCs subpopulation (% EPCs/HSCs) were significantly increased in the HCC patients compared to the controls. Our finding appears to be keeping with results published by Otto et al [32] who demonstrated that for a normal liver, high rate of HSCs together with low rate of EPCs is the standard. Yet, the occurrence of severe pathologic process within the liver, such as cirrhosis and particularly malignancy, inverses the relations between these cells leading to declining rates of hematopoietic cells and expanding rates of EPCs.…”
Section: Discussionsupporting
confidence: 93%
“…were defined by the phenotype of CD34 þ CD133 þ CD45and quantified as a percentage of the total white blood cells population (%HSCs/WBCs). The EPCs were defined by the phenotype of CD144 þ CD34 þ CD133 þ CD45 -, and quantified as percentage from the HSCs subpopulation (% EPCs/ HSCs) [13,32,33].…”
Section: Flow Cytometric Detection Of the Circulating Hematopoietic Smentioning
confidence: 99%
“…This corroborates the report of a study on 150 hepatocellular carcinoma patients, where increasing grading from I to III was accompanied by a gradual decrease in EPCs proportion in the patient's blood. 35 Our data are in line with the spatial and temporal evaluation of EPC contribution in tumor neovasculature described in experimental cancer models. 36 As evaluated by microscopy and flow cytometry, initially high proportion of BM-derived green fluorescence protein-positive EPCs were over time ''diluted'' by nonYBM-derived green fluorescence protein-negative ECs.…”
Section: Discussionsupporting
confidence: 86%
“…The hematopoietic stem cells could be recognized by the phenotype of CD34+,133+,45dim and the endothelial progenitor cells by additional expression of the cell surface marker CD309. The combination of hematopoietic stem cells and endothelial progenitor cells is believed to be essential for HCC tumor devalopment, growth, metastasses and recurrence [18,[25][26][27]31]. HCC cytokines, such as vascular endothelial growth factor stimulates the cell proliferation and enhances vascular permeability.…”
Section: Discussionmentioning
confidence: 99%
“…The VEGF is known to be the most potent angiogenesis factor and the stimulator of endothelial progenitor cells proliferation [21][22][23]27,28]. The association between the HCC development and the enhanced level of serum vascular endothelial growth factor concentration is indicated by numerous studies [25,26,30,31]. Some report also an association of the increased serumVEGF level concentration with the microvascular invasion of the tumor to the surrounding vessels [14,20,24,27].…”
Section: Discussionmentioning
confidence: 99%